2014
DOI: 10.1021/ic402116j
|View full text |Cite
|
Sign up to set email alerts
|

Red/Near-Infrared Luminescence Tuning of Group-14 Element Complexes of Dipyrrins Based on a Central Atom

Abstract: A dipyrrin complex has been one of the most utilized fluorescent dyes, and a variety of dipyrrin complexes show intriguing functions based on the various coordination structures of the central element. We now report the synthesis, structure, and photophysical properties of germanium and stannane complexes of the N2O2-type tetradentate dipyrrin, L·Ge and L·Sn, which are heavier analogues of the previously reported dipyrrin silicon complex, L·Si. The central group-14 atoms of the monomeric complexes have geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…This distorted geometry is also observed in the axial plane defined by the O(1)–Sn–O(2) angle, the value of which is very close to 160° (Table ). On the other hand, the N(1)–Sn bond lengths are in accordance with the values reported previously for coordinative bonds in pentacoordinate tin‐containing dibutyl fragments , . Compound 1 has intermolecular hydrogen‐bond interactions (Figure ) between the oxygen atom from the ester fragment and the hydrogen atom of the indole group from tryptophan with a bond length of 2.076 Å and a N2–H ··· O1 angle of 169.49°.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This distorted geometry is also observed in the axial plane defined by the O(1)–Sn–O(2) angle, the value of which is very close to 160° (Table ). On the other hand, the N(1)–Sn bond lengths are in accordance with the values reported previously for coordinative bonds in pentacoordinate tin‐containing dibutyl fragments , . Compound 1 has intermolecular hydrogen‐bond interactions (Figure ) between the oxygen atom from the ester fragment and the hydrogen atom of the indole group from tryptophan with a bond length of 2.076 Å and a N2–H ··· O1 angle of 169.49°.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, all of the complexes show three doublets of doublets in the range δ = 2.65 to 4.46 ppm, assigned to the chiral proton 13‐H [ δ ≈ 4.3 ppm, 3 J ( 1 H, 1 H) ≈ 3, 10 Hz] and the diastereotopic protons of the methylene group C‐14 [ δ ≈ 3.5 and 2.9 ppm, 2 J ( 1 H, 1 H) ≈ 3, 14 and 9, 14 Hz, respectively]. All of these values agree with the values reported for the diphenyl and dibutyltin complexes of a series of Schiff bases obtained previously , , . Thus, the NMR data confirm the presence of N→Sn coordination in all of the complexes.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The germanium and tin complexes 8 and 9 were synthesized in a similar way (Table 1, entries 5 and 6). 10 X ray crystallographic analysis of 8 revealed that the germanium center adopted a trigonal bipyramidal (TBP) geometry similar to the silicon complex 7c but the geometry of 8 (τ 0.67) is more distorted from the ideal TBP structure than that of 7c (τ 0.82). In contrast, the tin complex 9 adopts a dimeric hexacoordinate structure.…”
mentioning
confidence: 99%
“…The association constant (K a ) was determined by spectral titration to be (7.3 2.3) 10 7 M 1 . The large value of K a is indicative of the negligible dissociation process of the complex.…”
mentioning
confidence: 99%